Travesía Fluvial y Reducciones Jesuíticas En La Ribera Del Río Uruguay - Negrette, Angela Sanchez (Tempo da Ciência, 2000)
The rupture occurred by the expulsion of the Jesuits in 1767 has made various questions about how defined and established the city as part of the thirty people system path; situation synthesizing as the existence of a single Jesuit model. Since that question, this study aims to verify the definition of the path of the coastal peoples on the Uruguay river and the relation with the port activity.